Morphological method of expressive and stylistic meanings of anthroponyms formation on the example of Russian, Kazakh and Turkish languages (Journal of Oriental Studies, 2016)
in this article we analyzed the function of “diminutive” suffixes. the major of suffixes and affixes which help to form own informal and formal names in russian, Kazakh and turkish languages were pointed out. We underlined the characteristic of informal and formal personal names by locality (city, village).
Keywords: anthroponyms; official names; informal names